Modified sodium bicarbonate foaming agent and preparation method thereof
By using a low melting point coating agent to coat nano-grade sodium bicarbonate, it improves its thermal decomposition temperature and decomposition rate, it solves the problem that sodium bicarbonate is difficult to apply to general plastics, achieves a more efficient foaming effect and improves environmental protection .
Patent Information
- Application Number
- CN202411771316.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to the low decomposition temperature of ordinary specifications, sodium bicarbonate is difficult to be used in foaming of general plastics, and existing chemical foaming agents such as azodiformamide have environmental protection and safety problems.
Use low melting point coating agents such as dodecyl mercaptan, catechol and resorcinol to coat nano-grade sodium bicarbonate to increase its thermal decomposition temperature and decomposition rate to form modified sodium bicarbonate foam agent.
The thermal decomposition temperature and decomposition rate of the modified sodium bicarbonate foaming agent are improved, making it suitable for foaming of general-purpose plastics, and the environmental protection and stability are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of chemical foaming agents, and in particular to a modified sodium bicarbonate foaming agent and a preparation method thereof. Background Art
[0002] With the widespread application of foaming materials, foaming agents, as a key factor in the preparation process of foaming materials, have received more and more attention. Foaming agents can be divided into physical foaming agents and chemical foaming agents. At present, the common chemical foaming agents on the market are azodicarbonamide and foaming microspheres. Azodicarbonamide causes serious pollution during the production process. After decomposition, formamide will be produced, which puts great pressure on the environmental protection. In addition, an unpleasant ammonia smell will be produced during the application process. The above defects have greatly restricted the application of azodicarbonamide.
[0003] Sodium bicarbonate is a cheap, easily available, and environmentally friendly endothermic foaming agent that generates carbon dioxide and water when heated. The decomposition temperature of ordinary sodium bicarbonate is 50-270°C, while the processing temperature of general plastics is 180-220°C. When ordinary sodium bicarbonate is used as a foaming material for general plastics, most of the sodium bicarbonate has decomposed before the plastic begins to melt, so ordinary sodium bicarbonate is difficult to apply to general plastics. Summary of the invention
[0004] In order to solve the problem that ordinary specifications of sodium bicarbonate are difficult to apply to general plastics, the present application provides a modified sodium bicarbonate foaming agent, which uses a substance with a melting temperature lower than the decomposition temperature of nano-scale sodium bicarbonate to coat the nano-scale sodium bicarbonate, thereby increasing the initial decomposition temperature and the final decomposition temperature of the foaming agent, and also increasing the average decomposition rate of the modified sodium bicarbonate foaming agent.
[0005] In the first aspect, the present application provides a modified sodium bicarbonate foaming agent, which adopts the following technical solution: A modified sodium bicarbonate foaming agent comprises the following components in parts by weight: 50-90 parts of sodium bicarbonate, 5-45 parts of a coating agent, and 1-10 parts of a dehumidifying isolation agent; The average particle size of the sodium bicarbonate is 10-500nm; The coating agent includes one of n-docosyl mercaptan, catechol and resorcinol.
[0006] By adopting the above technical scheme, the decomposition temperature of sodium bicarbonate with an average particle size of 10-500nm is above 130°C, while the melting points of n-docosyl mercaptan are -7°C, the melting points of catechol are about 105°C, and the melting points of resorcinol are about 110-114°C, and the melting points of the coating agents are all lower than the decomposition temperature of sodium bicarbonate. Among them, although the melting points of n-docosyl mercaptan are -7°C, it is still solid at room temperature, mainly because the molecular chain of n-docosyl mercaptan is longer, which leads to relatively strong van der Waals forces between molecules. These forces make the molecules closely arranged in the solid state to form a stable crystal structure. Even above the melting point, if the temperature rises not quickly enough or there is not enough external energy input to overcome these intermolecular forces, the material may still remain in a solid state. When sodium bicarbonate is coated by the coating agent, the heat conducted to sodium bicarbonate is reduced. The activation energy of the thermal decomposition reaction of sodium bicarbonate is increased. In this way, the thermal decomposition temperature of the modified sodium bicarbonate foaming agent is greatly increased, and it can be used in the foaming field of general plastics.
[0007] In addition, the hydrocarbon chain of n-docosyl mercaptan and the benzene ring of catechol and resorcinol are all non-polar groups, which can be well combined with sodium bicarbonate. In addition, the thiol group of n-docosyl mercaptan and the phenolic hydroxyl group of catechol and resorcinol are all weakly acidic groups, which can more easily react with sodium bicarbonate when the temperature reaches the decomposition temperature of the modified sodium bicarbonate foaming agent, promote the decomposition of sodium bicarbonate into carbon dioxide, and increase the average decomposition rate of the modified sodium bicarbonate foaming agent.
[0008] The present application tightly wraps nano-scale sodium bicarbonate by coating agents such as n-docosyl mercaptan, catechol and resorcinol, thereby increasing the activation energy of the thermal decomposition reaction of sodium bicarbonate, thereby increasing the thermal decomposition temperature of the sodium bicarbonate foaming agent, and can be well applied to the foaming of general plastics. In addition, the thiol group of n-docosyl mercaptan and the phenolic hydroxyl groups of catechol and resorcinol can more easily react with sodium bicarbonate when the foaming agent decomposes, promote more carbon dioxide production, and increase the average decomposition rate of the modified sodium bicarbonate foaming agent.
[0009] Preferably, the mass ratio of the n-docosyl mercaptan to the sodium bicarbonate is (25-40):70.
[0010] By adopting the above technical solution, if the content of n-docosyl mercaptan is too low, the coating effect on sodium bicarbonate will be insufficient, and sodium bicarbonate will be easily affected by the external environment, thereby reducing the stability of the foaming agent. In addition, during the foaming process, the thiol groups in the n-docosyl mercaptan with too low a content are also less, and when decomposed, the promoting effect of n-docosyl mercaptan on sodium bicarbonate is also low.
[0011] If the content of n-docosyl mercaptan is too high, there are too many thiol groups, which may cause the sodium bicarbonate reaction to be too violent and difficult to control, and instead reduce the initial decomposition temperature of the modified sodium bicarbonate.
[0012] Preferably, the mass ratio of the catechol to the sodium bicarbonate is (15-35):70.
[0013] By adopting the above technical solution, if the content of catechol is too low, the coating effect on sodium bicarbonate will be insufficient, and sodium bicarbonate will be easily affected by the external environment, thereby reducing the stability of the foaming agent. In addition, during the foaming process, the phenolic hydroxyl group in the catechol with too low a content is also less, and when decomposing, the promoting effect of catechol on sodium bicarbonate is also low.
[0014] If the content of catechol is too high and there are too many phenolic hydroxyl groups, the sodium bicarbonate reaction may be too violent and difficult to control, which will reduce the initial decomposition temperature of the modified sodium bicarbonate.
[0015] Preferably, the mass ratio of the resorcinol to the sodium bicarbonate is (10-30):70.
[0016] By adopting the above technical solution, if the content of resorcinol is too low, the coating effect on sodium bicarbonate will be insufficient, and sodium bicarbonate will be easily affected by the external environment, thereby reducing the stability of the foaming agent. In addition, during the foaming process, the phenolic hydroxyl group in the resorcinol with too low a content is also less, and when decomposing, the promoting effect of resorcinol on sodium bicarbonate is also low.
[0017] If the content of resorcinol is too high and there are too many phenolic hydroxyl groups, the sodium bicarbonate reaction may be too violent and difficult to control, which will in turn reduce the initial decomposition temperature of the modified sodium bicarbonate.
[0018] Preferably, the coating agent is a mixture of n-docosyl mercaptan, catechol and resorcinol.
[0019] By adopting the above technical scheme, compared with using one of n-docosanthiol, catechol and resorcinol alone, a mixture of the three is selected as a coating agent to achieve a higher decomposition temperature and decomposition rate. This may be because on the one hand, the different melting points of the three are more conducive to reducing the conductive heat, and at the same time, they can better promote the decomposition of sodium bicarbonate in a wide range of thermal decomposition stages to obtain a suitable decomposition rate. On the other hand, the aromatic structure of catechol and the linear structure of n-docosanthiol are combined to achieve molecular shielding and molecular weight entanglement. While catechol and resorcinol provide non-polar groups, the steric activity between benzene ring molecules is enhanced based on the hydroxyl structure at different positions, which is beneficial to the distribution of n-docosanthiol molecular chains therein, and can achieve better coating of sodium bicarbonate.
[0020] Preferably, the mass ratio of n-docosyl mercaptan, catechol and resorcinol is (5-8): (10-15): (8-12).
[0021] By adopting the above technical solution, the mass ratio ensures the relative balance of the three components in the mixture. n-Dioctanol mercaptan, catechol and resorcinol each have unique chemical properties and physical characteristics. They can give full play to their respective advantages in this ratio to form a synergistic effect. The mixture at this ratio can more effectively wrap the sodium bicarbonate particles, reduce their contact with the external environment, and thus improve their thermal stability. This enables the foaming agent to maintain stable performance at higher temperatures and meet the needs of more types of plastic foaming. The three components will gradually release their effects in a certain order and rate during the decomposition process, making the decomposition process of sodium bicarbonate more stable and controllable. This helps to obtain a more uniform and delicate pore structure and improve the quality and performance of foamed products.
[0022] In a second aspect, the present application provides a method for preparing a modified sodium bicarbonate foaming agent, using the following technical solution: A method for preparing a modified sodium bicarbonate foaming agent is used for preparing the modified sodium bicarbonate foaming agent, comprising the following steps: adding sodium bicarbonate, a coating agent and a dehumidifying isolation agent into a mixing container according to the formula amount, stirring and heating until the coating agent is melted, and continuing to stir for a period of time to obtain the modified sodium bicarbonate foaming agent.
[0023] By adopting the above technical solution, the preparation method is relatively simple. It only needs to add the raw materials into the mixing container according to the formula amount, stir and heat until the coating agent melts, and then continue to stir for a period of time. This simplified process reduces the production difficulty and improves the production efficiency. After melting, the coating agent can be evenly coated on the surface of the sodium bicarbonate particles to form a protective film. This coating effect not only increases the thermal decomposition temperature of sodium bicarbonate, but also enhances its moisture resistance, thereby extending the storage life of the foaming agent.
[0024] Preferably, when the coating agent is n-docosyl mercaptan, the stirring heating temperature is 50-80° C., the stirring heating rate is 10-15° C. / min, and after the n-docosyl mercaptan is melted, the stirring time is 10-30 min.
[0025] By adopting the above technical solution, at a higher temperature, the fluidity of n-docosyl mercaptan increases, and it can be more evenly covered on the surface of sodium bicarbonate particles. Rapid heating (10-15℃ / min) can ensure that n-docosyl mercaptan quickly absorbs a large amount of heat in a short period of time, thereby quickly melting. This helps to quickly form a uniform coating during the mixing process.
[0026] If the stirring time is too short, n-docosyl mercaptan may not be able to fully and evenly cover the surface of the sodium bicarbonate particles. This will result in some sodium bicarbonate particles being exposed, failing to achieve the desired coating effect, and thus affecting the stability and performance of the foaming agent. Appropriate stirring time helps ensure sufficient contact and bonding between the coating agent and the sodium bicarbonate particles, thereby improving the coating efficiency and quality.
[0027] Preferably, when the coating agent is catechol, after the catechol is melted, the stirring time is 25-45 minutes.
[0028] By adopting the above technical solution, if the stirring time is too short, catechol may not be able to fully and evenly cover the surface of the sodium bicarbonate particles. This will cause some sodium bicarbonate particles to be exposed, and the expected coating effect cannot be achieved, thereby affecting the stability and performance of the foaming agent. Appropriate stirring time helps to ensure sufficient contact and bonding between the coating agent and the sodium bicarbonate particles, thereby improving the coating efficiency and quality. And because the melting point of catechol is higher than that of n-docosyl mercaptan, the stirring time is relatively longer.
[0029] Preferably, when the coating agent is resorcinol, after the resorcinol is melted, the stirring time is 30-50 minutes.
[0030] By adopting the above technical solution, resorcinol may not be fully and evenly covered on the surface of sodium bicarbonate particles. This will cause some sodium bicarbonate particles to be exposed, failing to achieve the expected coating effect, and thus affecting the stability and performance of the foaming agent. Appropriate stirring time helps to ensure sufficient contact and bonding between the coating agent and the sodium bicarbonate particles, thereby improving the coating efficiency and quality. And because the melting temperature of resorcinol is higher than that of catechol, the stirring time is relatively longer.
[0031] In summary, this application has the following beneficial effects: Since the present application adopts a coating agent such as n-docosyl mercaptan, catechol and resorcinol to tightly wrap the nano-scale sodium bicarbonate, the activation energy of the thermal decomposition reaction of sodium bicarbonate is increased, thereby increasing the thermal decomposition temperature of the sodium bicarbonate foaming agent, and can be well applied to the foaming of general plastics. In addition, the thiol group of n-docosyl mercaptan and the phenolic hydroxyl groups of catechol and resorcinol can more easily react with sodium bicarbonate when the foaming agent decomposes, promote more carbon dioxide production, and increase the average decomposition rate of the modified sodium bicarbonate foaming agent; When adding n-docosyl mercaptan, the application can ensure that n-docosyl mercaptan absorbs a large amount of heat in a short time by rapidly increasing the temperature (10-15°C / min), thereby rapidly melting. This helps to quickly form a uniform coating layer during the mixing process. DETAILED DESCRIPTION
[0032] The raw materials in this application include the following parts: Sodium bicarbonate: a commercially available product with CAS number 144-55-8; n-Docosyl mercaptan: a commercial product with CAS number 7773-83-3; Catechol: a commercially available product with CAS number 120-80-9 is used; Resorcinol: a commercially available product with CAS number 108-46-3; There are many types of dehumidification isolation agents, including calcium carbonate, calcium oxide, magnesium hydroxide, calcium hydroxide, kaolin, etc. selected in this application. This application only uses a commercially available calcium carbonate product with CAS No. 471-34-1 as an example.
[0033] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0034] Example 1 A method for preparing a modified sodium bicarbonate foaming agent comprises the following steps: 70 g of sodium bicarbonate, 35 g of n-docosyl mercaptan and 5 g of calcium carbonate were added to a mixing container, the average particle size of the sodium bicarbonate was 200 nm, and the temperature was raised to 70° C. with stirring at a heating rate of 15° C. / min. At this time, the n-docosyl mercaptan was melted, and stirring was continued for 30 min to obtain a modified sodium bicarbonate foaming agent.
[0035] Example 2-3 Example 2-3 Based on the preparation method of Example 1, the content of each component of the modified sodium bicarbonate foaming agent was adjusted, and the specific adjustment is shown in Table 1.
[0036] Comparative Example 1-2 Comparative Example 1-2 Based on the preparation method of Example 1, the content of each component of the modified sodium bicarbonate foaming agent was adjusted, and the specific adjustment is shown in Table 1.
[0037] Table 1 Contents and performance test table of each component of modified sodium bicarbonate foaming agent of Examples 1-3 and Comparative Examples 1-2
[0038] Performance testing The modified sodium bicarbonate foaming agents of Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests, and the test results are shown in Table 1.
[0039] 1. Initial decomposition temperature, end decomposition temperature and average decomposition rate Take 8 mg of modified sodium bicarbonate foaming agent sample and conduct thermogravimetric analysis (TG) test, heating from 30℃ to 250℃, heating rate 10℃ / min, nitrogen protection, gas flow rate 20mL / min. Differentiate the TG curve once to find the average decomposition rate dv / dt.
[0040] Since the processing temperature of general plastics is 180-220°C, the higher the decomposition temperature range of the foaming agent sample is in the range of 180-220°C, the better.
[0041] The average decomposition rate is related to the instantaneous gas evolution of the foaming agent. The higher the average decomposition rate, the higher the instantaneous gas evolution; the lower the average decomposition rate, the lower the instantaneous gas evolution. The instantaneous gas evolution of the foaming agent directly affects the density and pore structure of the plastic product. If the instantaneous gas evolution is too large, the density of the plastic product may be too low and the pores may be too large, thereby affecting its mechanical and physical properties, such as strength, hardness, and wear resistance. On the contrary, if the instantaneous gas evolution is too small, sufficient pores may not be formed, resulting in poor lightweighting of the plastic product. After testing, it was found that the average decomposition rate is preferably in the range of 12-28% / min, and more preferably in the range of 19.5-22.5% / min.
[0042] Referring to Table 1, by comparing Examples 1-3 with Comparative Examples 1-2, it can be seen that compared with Comparative Example 2, the initial decomposition temperature, the final decomposition temperature and the average decomposition rate of Examples 1-3 are much higher than those of Comparative Example 2, indicating that n-docosanyl mercaptan can be well combined with sodium bicarbonate, thereby increasing the decomposition temperature and the average decomposition rate of the modified sodium bicarbonate foaming agent, and better applied to the foaming field of general plastics.
[0043] In addition, by comparing Examples 1-3, it is found that Example 1 has the best performance, so Example 1 is preferred.
[0044] Embodiment 4-7 Example 4-7 Based on the preparation method of Example 1, the average particle size of sodium bicarbonate is adjusted, and the specific adjustment is shown in Table 2.
[0045] The modified sodium bicarbonate foaming agents of Examples 4-7 were subjected to the above performance tests, and the test results are shown in Table 2.
[0046] Table 2 Average particle size and performance test table of sodium bicarbonate in Example 1 and Examples 4-7
[0047] Referring to Table 2, it can be seen from the comparison between Example 1 and Examples 4-7 that when the average particle size of sodium bicarbonate continues to increase, the initial decomposition temperature and the end decomposition temperature continue to increase, and the average decomposition rate shows a downward trend. This may be because when the average particle size of sodium bicarbonate continues to increase, the total surface area of sodium bicarbonate continues to decrease, and the decomposition difficulty of sodium bicarbonate continues to increase, thereby affecting the increase of the initial decomposition temperature and the end decomposition temperature, and reducing the average decomposition rate.
[0048] Embodiment 8-11 Examples 8-11 are based on the preparation method of Example 1, except that the amount of n-docosyl mercaptan added is adjusted. The specific adjustments are shown in Table 3.
[0049] The modified sodium bicarbonate foaming agents of Examples 8-11 were subjected to the above performance tests, and the test results are shown in Table 3.
[0050] Table 3 Addition amount and performance test table of n-docosyl mercaptan of Example 1 and Examples 8-11
[0051] Referring to Table 3, by comparing Example 1 with Examples 8-11, it can be seen that as the amount of n-docosyl mercaptan added increases, the initial decomposition temperature shows a trend of increasing and approaching stability, the end decomposition temperature shows a trend of first increasing and then decreasing, and the average decomposition rate shows a trend of increasing. This may be due to the fact that as the amount of n-docosyl mercaptan added increases, the coating effect of n-docosyl mercaptan on sodium bicarbonate increases, thereby increasing the initial decomposition temperature, the end decomposition temperature and the average decomposition rate of the modified sodium bicarbonate foaming agent; when the amount of n-docosyl mercaptan added exceeds a certain range, there are too many thiol groups, which may cause the sodium bicarbonate reaction to be too violent and difficult to control, thereby reducing the end decomposition temperature of the modified sodium bicarbonate foaming agent.
[0052] Examples 12-15 Examples 12-15 are based on the preparation method of Example 1, except that the stirring heating temperature and heating rate after adding n-docosyl mercaptan are adjusted. The specific adjustments are shown in Table 4.
[0053] The modified sodium bicarbonate foaming agents of Examples 12-15 were subjected to the above performance tests, and the test results are shown in Table 4.
[0054] Table 4 Stirring heating temperature and heating rate after adding n-docosyl mercaptan and performance test table of Example 1 and Examples 12-15
[0055] Referring to Table 4, by comparing Example 1 with Examples 12-15, it can be seen that as the heating rate after the addition of n-docosanyl mercaptan increases, the initial decomposition temperature, the final decomposition temperature and the average decomposition rate continue to increase. This may be because as the heating rate after the addition of n-docosanyl mercaptan increases, n-docosanyl mercaptan rapidly absorbs a large amount of heat in a short period of time, thereby rapidly melting, which helps to quickly form a uniform coating layer during the mixing process.
[0056] Examples 16-17 In Examples 16-17, based on the preparation method of Example 1, the stirring time after melting n-docosyl mercaptan was adjusted, and the specific adjustment is shown in Table 5.
[0057] Comparative Examples 3-4 Comparative Example 3-4 Based on the preparation method of Example 1, the stirring time after melting n-docosyl mercaptan was adjusted, and the specific adjustment is shown in Table 5.
[0058] The modified sodium bicarbonate foaming agents of Examples 16-17 and Comparative Examples 3-4 were subjected to the above performance tests, and the test results are shown in Table 5, respectively.
[0059] Table 5 Stirring time and performance test table of n-docosyl mercaptan after melting of Example 1, Examples 16-17 and Comparative Examples 3-4
[0060] Referring to Table 5, it can be seen from the comparison of Example 1, Examples 16-17 and Comparative Examples 3-4 that as the stirring time after the melting of n-docosanyl mercaptan continues to increase, the initial decomposition temperature, the final decomposition temperature and the average decomposition rate show a trend of continuously increasing and then tending to a stable state. It is possible that the continuous increase in the stirring time after the melting of n-docosanyl mercaptan helps to ensure sufficient contact and bonding between n-docosanyl mercaptan and the sodium bicarbonate particles, thereby improving the coating efficiency and quality.
[0061] Examples 18-22 Example 18 Based on the preparation method of Example 1, 35 g of n-docosyl mercaptan was replaced with 30 g of catechol. After the catechol was melted, stirring was continued for 45 minutes, and the other conditions remained unchanged.
[0062] In Examples 19-22, based on the preparation method of Example 18, the amount of catechol added was adjusted. The specific adjustments are shown in Table 6.
[0063] The modified sodium bicarbonate foaming agents of Examples 18-22 were subjected to the above performance tests, and the test results are shown in Table 6.
[0064] Table 6 Addition amount and performance test table of catechol in Example 1 and Examples 18-22
[0065] Referring to Table 6, it can be seen from the comparison between Example 1 and Examples 18-22 that catechol can also be used in the present application.
[0066] As the amount of catechol added continues to increase, the initial decomposition temperature and the average decomposition rate both show an increasing trend, and the final decomposition temperature shows a trend of first increasing and then decreasing. This may be because as the amount of catechol added continues to increase, the coating effect of catechol on sodium bicarbonate continues to increase, thereby increasing the initial decomposition temperature, final decomposition temperature and average decomposition rate of the modified sodium bicarbonate foaming agent; when the amount of catechol added exceeds a certain range, there are too many phenolic hydroxyl groups, which may cause the sodium bicarbonate reaction to be too violent and difficult to control, thereby reducing the final decomposition temperature of the modified sodium bicarbonate foaming agent.
[0067] Embodiment 23-24 In Examples 23-24, based on the preparation method of Example 18, the stirring time after the catechol is melted is adjusted, and the specific adjustments are shown in Table 7.
[0068] Comparative Examples 5-6 Comparative Example 5-6 is based on the preparation method of Example 18, and the stirring time after the catechol is melted is adjusted. The specific adjustment is shown in Table 7.
[0069] The modified sodium bicarbonate foaming agents of Examples 23-24 and Comparative Examples 5-6 were subjected to the above performance tests, and the test results are shown in Table 7, respectively.
[0070] Table 7 Stirring time and performance test table of catechol after melting in Example 18, Examples 23-24 and Comparative Examples 5-6
[0071] Referring to Table 7, it can be seen from the comparison of Example 18, Examples 23-24 and Comparative Examples 5-6 that as the stirring time after the catechol is melted continues to increase, the initial decomposition temperature, the end decomposition temperature and the average decomposition rate show a trend of rising continuously and then tending to a stable state. It is possible that the increasing stirring time after the catechol is melted helps to ensure sufficient contact and bonding between the catechol and the sodium bicarbonate particles, thereby improving the coating efficiency and quality.
[0072] Examples 25-29 Example 25 Based on the preparation method of Example 1, 35 g of n-docosyl mercaptan was replaced with 20 g of resorcinol. After the resorcinol was melted, stirring was continued for 50 minutes, and the other conditions remained unchanged.
[0073] In Examples 26-29, based on the preparation method of Example 25, the amount of resorcinol added was adjusted. The specific adjustments are shown in Table 8.
[0074] The modified sodium bicarbonate foaming agents of Examples 25-29 were subjected to the above performance tests, and the test results are shown in Table 8 respectively.
[0075] Table 8 Addition amount and performance test table of resorcinol in Example 1 and Examples 25-29
[0076] Referring to Table 8, it can be seen from the comparison between Example 1 and Examples 25-29 that resorcinol can also be used in the present application.
[0077] As the amount of resorcinol added continues to increase, the initial decomposition temperature and the average decomposition rate both show an increasing trend, and the final decomposition temperature shows a trend of first increasing and then decreasing. This may be because as the amount of resorcinol added continues to increase, the coating effect of resorcinol on sodium bicarbonate continues to increase, thereby increasing the initial decomposition temperature, final decomposition temperature and average decomposition rate of the modified sodium bicarbonate foaming agent; when the amount of resorcinol added exceeds a certain range, there are too many phenolic hydroxyl groups, which may cause the sodium bicarbonate reaction to be too violent and difficult to control, thereby reducing the final decomposition temperature of the modified sodium bicarbonate foaming agent.
[0078] Examples 30-31 In Examples 30-31, based on the preparation method of Example 25, the stirring time after the resorcinol is melted is adjusted, and the specific adjustments are shown in Table 9.
[0079] Comparative Examples 7-8 Comparative Example 7-8 is based on the preparation method of Example 25, and the stirring time after the resorcinol is melted is adjusted. The specific adjustment is shown in Table 9.
[0080] The modified sodium bicarbonate foaming agents of Examples 30-31 and Comparative Examples 7-8 were subjected to the above performance tests, and the test results are shown in Table 9, respectively.
[0081] Table 9 Stirring time and performance test table of resorcinol after melting in Example 25, Examples 30-31 and Comparative Examples 7-8
[0082] Referring to Table 9, it can be seen from the comparison of Example 25, Examples 30-31 and Comparative Examples 7-8 that as the stirring time after the resorcinol is melted continues to increase, the initial decomposition temperature, the end decomposition temperature and the average decomposition rate show a trend of rising and then tending to a stable state. It is possible that the increasing stirring time after the resorcinol is melted helps to ensure sufficient contact and bonding between the resorcinol and the sodium bicarbonate particles, thereby improving the coating efficiency and quality.
[0083] Examples 32-34 Example 32 Based on the preparation method of Example 18, 30 g of catechol is replaced with 30 g of a mixture of n-docosanthiol, catechol and resorcinol, the mass ratio of n-docosanthiol, catechol and resorcinol is 5:10:12, and the other conditions remain unchanged.
[0084] Example 33 Based on the preparation method of Example 32, the mass ratio of n-docosyl mercaptan, catechol and resorcinol is adjusted to 7:12:10, and the other conditions remain unchanged.
[0085] Example 34 Based on the preparation method of Example 32, the mass ratio of n-docosyl mercaptan, catechol and resorcinol is adjusted to 8:15:8, and the other conditions remain unchanged.
[0086] The modified sodium bicarbonate foaming agents of Examples 32-34 were subjected to the above performance tests, and the test results are shown in Table 10 respectively.
[0087] Table 10 Performance test table of Example 1, Example 18, Example 25 and Examples 32-34
[0088] Referring to Table 10, it can be seen from the comparison of Examples 1, 18, 25 and 32-34 that, compared with the use of one of n-docosanthiol, catechol and resorcinol alone, the mixture of the three is selected as the coating agent to achieve a higher decomposition temperature and decomposition rate. This may be because, on the one hand, the different melting points of the three are more conducive to reducing the heat conduction, and at the same time, they can better promote the decomposition of sodium bicarbonate in a wide range of thermal decomposition stages to obtain a suitable decomposition rate. On the other hand, the aromatic structure of catechol and the linear structure of n-docosanthiol are combined to achieve molecular shielding and molecular weight entanglement. While catechol and resorcinol provide non-polar groups, the steric activity between benzene ring molecules is enhanced based on the hydroxyl structure at different positions, which is beneficial to the distribution of n-docosanthiol molecular chains therein, and can achieve better coating of sodium bicarbonate.
[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A modified sodium bicarbonate foaming agent, characterized in that, The invention comprises the following components in parts by weight: 50-90 parts of sodium bicarbonate, 5-45 parts of coating agent, and 1-10 parts of dehumidifying isolation agent; The average particle size of the sodium bicarbonate is 10-500nm; The coating agent includes one of n-docosyl mercaptan, catechol and resorcinol.
2. The modified sodium bicarbonate foaming agent according to claim 1, characterized in that: The mass ratio of the n-docosyl mercaptan to the sodium bicarbonate is (25-40):
70.
3. The modified sodium bicarbonate foaming agent according to claim 1, characterized in that: The mass ratio of the catechol to the sodium bicarbonate is (15-35):
70.
4. The modified sodium bicarbonate foaming agent according to claim 1, characterized in that: The mass ratio of the resorcinol to the sodium bicarbonate is (10-30):
70.
5. The modified sodium bicarbonate foaming agent according to claim 1, characterized in that: The coating agent is a mixture of n-docosyl mercaptan, catechol and resorcinol.
6. The modified sodium bicarbonate foaming agent according to claim 5, characterized in that: The mass ratio of n-docosyl mercaptan, catechol and resorcinol is (5-8): (10-15): (8-12).
7. The preparation method of the modified sodium bicarbonate foaming agent described in any one of claims 1 to 6, characterized in that: Sodium bicarbonate, a coating agent and a dehumidifying isolation agent are added into a mixing container according to the formula amount, stirred and heated until the coating agent is melted, and then stirred for a period of time to obtain a modified sodium bicarbonate foaming agent.
8. The preparation method of modified sodium bicarbonate foaming agent according to claim 7, characterized in that: When the coating agent is n-docosyl mercaptan, the stirring heating temperature is 50-80° C., the stirring heating rate is 10-15° C. / min, and after the n-docosyl mercaptan is melted, the stirring time is 10-30 min.
9. The preparation method of modified sodium bicarbonate foaming agent according to claim 7, characterized in that: When the coating agent is catechol, after the catechol is melted, the stirring time is 25-45 minutes.
10. The method for preparing the modified sodium bicarbonate foaming agent according to claim 7, characterized in that: When the coating agent is resorcinol, after the resorcinol is melted, the stirring time is 30-50 minutes.
Citation Information
Patent Citations
Modified foaming agent of polypropylene foaming material and preparation method modified foaming agent
CN103881238A
Novel environmentally friendly foaming agent and preparation method thereof
CN109575347A
Environment-friendly chemical foaming agent and preparation method thereof
CN112724454A
White foaming agent with delayed foaming function and preparation method thereof
CN113372603A
Production of polyolefin resin foamed sheet
JP1989062334A
Cited By
EPDM (Ethylene-Propylene-Diene Monomer) foaming material with low odor and high mechanical property and preparation method thereof
CN119875251A